A Practical Approach to Public Sector Reform: Following the Dollar in Reforming Road Maintenance. (25th July 2016) - Kaiser, Paul J.; Streatfeild, Jeremy
Abstract : This article presents a new approach to designing public sector reform programmes, which we call a capacity map (CM). This approach focuses on the flow of public funds from the point of 'extraction' through to their 'disbursement', with specific attention to 'leakages' in that overall system. The CM is a modest attempt to provide development partners and their partner governments with a relatively simple, but effective, tool that complements other oft‐used tools in the programme design process. To elucidate the CM approach, development partner attempts to support the establishment, or reform of, road maintenance regimes are focused on. The CM unpacks the process of road maintenance to identify leakages in the overall road maintenance system, thus enabling development partners to focus on institutional root causes beyond a singular focus on insufficient funds. It is contended that this tool enables the programme designer to develop focused interventions, whether in roads or other infrastructure projects, that move beyond 'quick fixes' that may avoid the difficult questions and hard choices that need to be made for sustainable institutional and policy reform.